Ordovician graptolite biostratigraphy of the Röstånga-2 drill core (Scania, southern Sweden). (2nd July 2020) - Maletz, Jörg; Ahlberg, Per; Lundberg, Frans
ABSTRACT: The graptolite biostratigraphy of the 116.11-m-long Röstånga-2 drill core from Scania, southern Sweden, includes the Darriwilian (Middle Ordovician) Holmograptus lentus, Nicholsonograptus fasciculatus, Pterograptus elegans, Pseudamplexograptus distichus and Jiangxigraptus vagus biozones, and the lower Sandbian (Upper Ordovician) Nemagraptus gracilis Biozone. The early Darriwilian Komstad Limestone was not reached. The succession includes numerous levels of brecciated rocks and slickensides, suggesting considerable tectonic deformation and possible gaps. The boundary between the Almelund Shale Formation (below) and the Sularp Shale Formation (above) has been identified at 19.55–19.70 m, where the Fågelsång Phosphorite Bed has been identified tentatively in the Jiangxigraptus vagus Biozone. The first specimens of Nemagraptus gracilis appear higher in the succession. The international correlation of the Darriwilian graptolite succession is discussed.